Lúcio Cardoso, the eccentric subject - Vianna, Lúcia Helena (2005)
On the Lúcio Cardoso's Complete Diary, published in 1961, we can examine the multiples relations among the public and the private areas on the literary discourse. The Diary presents itself as one of the forms of the self discourse approach - where the subject constructs his own subjectivity.